Challenges in the diagnosis and control of female genital schistosomiasis in sub-Saharan Africa: an exemplar case report associated with mixed and putative hybrid schistosome infection in Nsanje District, Southern Malawi - Kayuni, Sekeleghe A.; Cunningham, Lucas J.; Kumwenda, Dingase; Mainga, Bright; Lally, David; Chammudzi, Priscilla; Kapira, Donales; Namacha, Gladys; Ntaba, Bessie; Chisale, Alice; Nchembe, Tereza; Kinley, Luis; et al. (Frontiers in Tropical Diseases, 2024)
Female genital schistosomiasis (FGS) remains an often overlooked chronic complication of urogenital schistosomiasis in adolescent girls and women. Moreover, the role of zoonotic or hybrid schistosome infection(s) is poorly appreciated, but is increasingly becoming an emerging public health concern in sub-Saharan Africa. In Southern Malawi, during the “Hybridization in UroGenital Schistosomiasis (HUGS)” study visit, we describe the case of a 33-year-old woman with suspected FGS who partook in a detailed external assessment with internal cervical examination using a portable colposcope. She provided several biological samples for analysis with traditional and molecular parasitological methods—urine, cervicovaginal lavage (CVL), cervical swabs, and external mass and cervical biopsies—alongside provision of detailed demographic information after a thorough medical history questionnaire and an in-depth interview. These samples were screened for the presence of Schistosoma ova on microscopy and DNA genotyping using a novel real-time PCR assay in parallel to pre-published probe-based PCR assays capable of identifying and discriminating up to six named Schistosoma species. A further molecular screen of sexually transmitted infections (STIs) including Trichomonas vaginalis, Chlamydia spp., and human papilloma virus (HPV) was conducted on her genital swab and CVL. Overt FGS was diagnosed on clinical colposcopy alongside inspection of the cervical biopsy by microscopy, real-time PCR, and histopathology. The urine filtration, microscopy and real-time PCR of the CVL and swab were negative. This evidences the typical diagnostic challenge, and cases such as this will pose an unmet need in satisfactory patient management. In addition to Schistosoma haematobium, the presence of the zoonotic species Schistosoma mattheei and concurrent STIs raise questions as to the long-term effectiveness of the current control strategies of the National Control Programme to eliminate schistosomiasis as a public health problem. Improved availability of and regular accessibility to praziquantel treatment for women at risk such as this are urgently needed. Furthermore, targeted health education, increased community awareness, and dovetailing of synergistic activities and strategies with other health stakeholders such as those in sexual and reproductive health, as well as HIV/AIDS programs in the Ministry of Health, are needed here and in neighboring countries.